2017
DOI: 10.1038/s41598-017-05411-z
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Variants of Maternal/Fetal Renin-Angiotensin System in Preeclampsia: A Hybrid Case-Parent/Mother-Control Study

Abstract: Preeclampsia (PE) is a common pregnancy-related complication, and polymorphisms in angiotensinogen (AGT), angiotensin-converting enzyme (ACE), and angiotensin II type 1 receptor (AT1R) are believed to contribute to PE development. We implemented a hybrid study to investigate the influence of maternal and fetal ACE I/D, ACE G2350A, AGT M235T, AGT T174M, and AT1R A1166C polymorphisms on PE in Han Chinese women. Polymorphisms were genotyped in 1,488 subjects (256 patients experiencing PE, along with their fetuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
10
0
4
Order By: Relevance
“…[ 60 ] Interestingly, AT1R 1166 C allele was revealed to play a significant role in PE development among Chinese pregnant women. [ 40 ] On the contrary, in some studies, there were no correlation between AT1R -1166 A/C polymorphism and susceptibility to PE. [ 29 , 35 , 51 ] In 2015, a systematic review and meta-analysis by Li et al showed the AT1R -1166 A/C polymorphism was not associated with PIH or PE among a pooled analysis of overall genetic models, [ 61 ] which was consistent with previous results of Zhao et al’ s study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] Interestingly, AT1R 1166 C allele was revealed to play a significant role in PE development among Chinese pregnant women. [ 40 ] On the contrary, in some studies, there were no correlation between AT1R -1166 A/C polymorphism and susceptibility to PE. [ 29 , 35 , 51 ] In 2015, a systematic review and meta-analysis by Li et al showed the AT1R -1166 A/C polymorphism was not associated with PIH or PE among a pooled analysis of overall genetic models, [ 61 ] which was consistent with previous results of Zhao et al’ s study.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of RAS is regulating placental development and uteroplacental blood circulation has also been recognized 12 . RAS in the utero‐placental unit of pregnant women affects placental intervillous blood flow and assist in local spiral arterial remodeling 13 . RAS imbalance may result in the potential failure of maternal spiral arterial remodeling and utero‐placental ischemia, ultimately leading to PIH 13 .…”
Section: Genetic Polymorphisms Of Pihmentioning
confidence: 99%
“…RAS in the utero‐placental unit of pregnant women affects placental intervillous blood flow and assist in local spiral arterial remodeling 13 . RAS imbalance may result in the potential failure of maternal spiral arterial remodeling and utero‐placental ischemia, ultimately leading to PIH 13 . Additionally, RAS monitors blood pressure and body fluids via enzymatic reactions that are controlled through a variety of enzymes and receptors, including renin, angiotensinogen (AGT), angiotensin‐converting enzyme (ACE), angiotensin I (ANG I), angiotensin II (ANG II), angiotensin II receptor type 1 (AT1R), and angiotensin II receptor type 2 (AT2R) 10 .…”
Section: Genetic Polymorphisms Of Pihmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II stimulates the secretion of aldosterone, which regulates uteroplacental vasoconstriction and blood pressure [9]. Previous studies have shown that an increase in uteroplacental blood pressure is associated with the development of PTB, preeclampsia, and spontaneous abortion [10,11,12].…”
Section: Introductionmentioning
confidence: 99%